Multiple squamous hyperplastic-fibrous inflammatory polyps of the oesophagus: a new feature of eosinophilic oesophagitis?. Issue 9 (4th September 2009) - Mulder, D J; Gander, S; Hurlbut, D J; Soboleski, D A; Smith, R G; Justinich, C J
Abstract : This report describes the unusual case of a 12-year-old boy with multiple polyps in the oesophagus and concurrent eosinophilic oesophagitis (EoE). Polyps were of a fibrous-inflammatory composition featuring eosinophils, mast cells, hyperplastic epithelium and fibrosis, which are all features described with EoE. EoE is an increasingly recognised clinicopathological disorder characterised by large numbers of eosinophils infiltrating the oesophageal mucosa. Polyps in the oesophagus are rare, have not previously been associated with EoE, and may represent a new feature of the disease.